2019
DOI: 10.1002/ccr3.1977
|View full text |Cite
|
Sign up to set email alerts
|

Bladder stone: “Must know” ultrasonographic signs

Abstract: Key Clinical Message Point‐of‐care ultrasonography by non‐radiology physicians has become a valuable bedside diagnostic tool. As urolithiasis is one of the commonest indications for sonographic examination, physicians need to be familiar with the characteristic features of stones, that is, acoustic shadowing on gray scale and twinkle artefact on color doppler imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…On gray-scale images, stones appear as hyperechoic or bright structures with a posterior “acoustic shadow”. Acoustic shadowing is the black area or signal void seen beyond structures that do not transmit ultrasound waves[34]. In the Doppler mode, stones exhibit “twinkling sign” or artifact, which refer to a rapidly alternating focus of color Doppler signals mimicking turbulent flow and is more pronounced with rougher stones.…”
Section: Common Sonographic Abnormalitiesmentioning
confidence: 99%
“…On gray-scale images, stones appear as hyperechoic or bright structures with a posterior “acoustic shadow”. Acoustic shadowing is the black area or signal void seen beyond structures that do not transmit ultrasound waves[34]. In the Doppler mode, stones exhibit “twinkling sign” or artifact, which refer to a rapidly alternating focus of color Doppler signals mimicking turbulent flow and is more pronounced with rougher stones.…”
Section: Common Sonographic Abnormalitiesmentioning
confidence: 99%
“…The sonographic appearance of the stone is affected by its density and composition. If the ultrasound probe frequency was too low or the uroliths were not in the ultrasound beam's direct path, the shadow cones linked with the bladder calculi may not be evident 6,9 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of bacteria because of cystitis can alter the urinary pH level and promote stone formation. It's worth mentioning that cystitis can also occur due to urolithiasis caused by the contact between the bladder wall and the calculus 9 . However, more studies can indicate its origin.…”
Section: Discussionmentioning
confidence: 99%
“…Around the same time, the patient developed gross haematuria, flank pain and mild acute Kidney Injury with a serum creatinine 1.3 mg/dL (baseline ~0.9). A renal sonogram was obtained which showed non-obstructing bilateral renal stones with the classic acoustic shadowing and twinkling sign3 figure 2. She did not have known history of nephrolithiasis and review of CT of the abdomen prior to transplant confirmed the same.…”
Section: Descriptionmentioning
confidence: 99%